Estimating impact of financial incentives on construction waste production - Pavopar, Milad (International Journal of Engineering and Technology, 2018)
Due to destructive environmental effects of construction wastes and increasing amount of these wastes that are in conflict with sustainable development objectives, it is essential to adopt solutions in order to reduce such wastes regarding environment preservation. This study was conducted to examine impact of financial incentives on reducing construction wastes using pairwise comparisons. According to professional opinions and experience of experts in building industry based on the 7-point Likert scale, mean responses obtained to 4.93, 4.83, and 4.73 for waste materials (stone, tile, ceramic), ready mix concrete waste, and EPS (Expanded Polystyrene) waste, respectively. On the other hand, reliability of research instrument obtained at 0.77 using Cronbachâ€™s alpha test. Moreover, it is seen that the studied materials in this research assigned 41% contribution of constructing costs to themselves; of them, fittings and tiles, ceramics and stone assigned the highest constructing cost to themselves with 12%contribution. In fact, waste of materials in projects under the â€œtotal priceâ€ contract 30-50% higher than projects under the â€œcost plusâ€ contract. Increasing number of floors and area of construction project lead to average reduction in waste of materials from 4.4% to 1.4%. Change in regional price of housing will changes materials used in construction based on different prices.Â Â